Produção e qualidade dos frutos de diferentes variedades de caqui, visando à industrialização - Pinheiro , Rubens V R; Nogueira da Costa , Aureliano; G de Souza , Antonio Carlos; Condé, Alcides R (Revista Ceres, 2025)
Six varieties of oriental persimmon (Diospyros kaki L.) were studied as to the following aspects: fruit weight produced per hectare; average fruit weight (g); percent total soluble solids (°Brix); pH; total titrable acids; and reducing sugars.